1995
DOI: 10.1080/02640419508732244
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aerobic versus anaerobic exercise on the relationship between reproductive hormones in men

Abstract: This study examined the effects of equal anaerobic and aerobic total work outputs on the relationship between reproductive hormones in men. Nine subjects performed three randomized trials on separate days: (1) 1 h period of rest (control), (2) 1 h continuous aerobic exercise (65% VO2 max), and (3) 1 h intermittent anaerobic exercise (which included 2 min exercise periods at 110% VO2 max). The total work output of the aerobic and anaerobic trials were equated. For the 8 h after each experimental trial, blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 23 publications
2
57
0
2
Order By: Relevance
“…In contrast, short-term, anabolic exercise often causes acute increases in testosterone levels (Cumming et al, 1986(Cumming et al, , 1987Hackney et al, 1995). Moreover, nutritional supplementation in conjunction with anabolic exercise augments androgen rises in healthy men (Chandler et al, 1994).…”
Section: Energetic Expenditurementioning
confidence: 99%
“…In contrast, short-term, anabolic exercise often causes acute increases in testosterone levels (Cumming et al, 1986(Cumming et al, , 1987Hackney et al, 1995). Moreover, nutritional supplementation in conjunction with anabolic exercise augments androgen rises in healthy men (Chandler et al, 1994).…”
Section: Energetic Expenditurementioning
confidence: 99%
“…However, while aerobic and anaerobic forms of exercise are commonly compared relative to biochemical [24][25][26][27][28][29] and hormonal [27,28,30,31] markers of performance, direct comparisons of their relative contributions to cardiac health are surprisingly lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The D+AT group did show an increase in testosterone concentrations in men relative to the D+ST group, when tested more than 48 h after the last exercise session. Other studies of increases in testosterone levels during aerobic exercise report that these effects are transient [15,16] . However, Grandys et al [24] reported a rise in circulating testosterone levels, measured more than 24 h after exercise, following a 5-wk aerobic training program.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that both aerobic and anaerobic exercise can increase testosterone levels [16] , but differences in the beta-adrenergic effects between resistance training and aerobic exercise [16] may have led to up-regulation of beta-adrenergic receptors and increased hepatic testosterone intake, decreasing circulating testosterone levels in the D+ST group in comparison to the D+AT group. In addition, Hackney et al [15] showed that resistance, but not aerobic, training disrupts the relationship between luteinizing hormone (LH) and testosterone production. Also, Nindl et al [26] found a decrease in the production of LH and Diet Plus Exercise Versus Diet Only a subsequent decline in overnight testosterone concentrations after resistance training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation